DEMOCRACY IN NIGERIA AND INDIA: A COMPARATIVE ANALYSIS OF CHALLENGES TO CONTEMPORARY DEMOCRATIC GOVERNMENT (Singaporean Journal of Business Economics and Management, 2015)
Democracy that is said to be exported is representative democracy which traces its origin to the western world and more specifically the US and Britain who are the fathers' of presidential and parliamentary democracies respectively that have dominated the rest of the world. The importers - Asia and Africa among others have had to face the challenges of adaptability according to the original models (American or British). Some of the challenges range from poverty, corruption, underdevelopment that is heavily alleged to the legacy of colonialism in these continents - Asia and Africa. In spite of all the odds, India defied the theories of democracy that development must come before democracy; but India had thriven amidst hardship, poverty, but good nationalist leaders that today India is a known existing democracy for decades as against Nigeria who virtually lacked the Indian - like nationalist leaders. Finally, exporters must be more realistic to consider that the terrain of importers is different in culture, national experience, and development from theirs.